The Role Of Computer Technology In Environmental Health Monitoring And Management - Paska Marto Hasugian (SEAN Institute, 2024)
Environmental health is gaining prominence on the global agenda due to the serious impact of increasing air, water and land pollution on human health. Computer technology offers a potential solution by enabling more accurate and efficient data collection, more comprehensive data analysis, and more informed decision making. This research aims to understand the role of computer technology in monitoring and managing environmental health in detail. Using qualitative methods, data from various sources is analyzed to provide in-depth understanding and recommendations for stakeholders. The research results show an increase in the use of computers and technology in monitoring, modeling and predicting environmental hazards, as well as their support for environmental health policy decision making. However, challenges such as cost, data privacy and coordination between institutions need to be overcome for this technology to provide maximum benefit to society as a whole.